2021
DOI: 10.1016/j.ijppaw.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatal infection caused by Cytauxzoon felis in a captive-reared jaguar (Panthera onca)

Abstract: Fatal infections with Cytauxzoon felis are common in domestic cats, and jaguars ( Panthera onca ) are believed carriers of this protozoan. Fatal C. felis infections have never been described in jaguars before. Thus, this study describes such an infection in a 5-month-old captive-reared jaguar that presented hyporexia and died at 26 days after the first clinical signs. During necropsy, samples were taken from several tissues, some were fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Neotropical wild felids likely play a role as reservoirs for Cytauxzoon in Brazil [33,34], probably presenting short and self-limiting schizogony as previously observed in bobcats (Lynx rufus), which act as reservoirs for C. felis in the USA [9]. As far as authors are concerned, fatal cytauxzoonosis has not been reported in domestic cats in Brazil, despite reports of fatal cytauxzoonosis in lions (Panthera leo) [35] and jaguars (Panthera onca) [36] in the country. Actually, despite the detection of piroplasms in cats' erythrocytes [20,37], schizonts have not been detected in domestic cats from Brazil so far.…”
Section: Discussionmentioning
confidence: 92%
“…Neotropical wild felids likely play a role as reservoirs for Cytauxzoon in Brazil [33,34], probably presenting short and self-limiting schizogony as previously observed in bobcats (Lynx rufus), which act as reservoirs for C. felis in the USA [9]. As far as authors are concerned, fatal cytauxzoonosis has not been reported in domestic cats in Brazil, despite reports of fatal cytauxzoonosis in lions (Panthera leo) [35] and jaguars (Panthera onca) [36] in the country. Actually, despite the detection of piroplasms in cats' erythrocytes [20,37], schizonts have not been detected in domestic cats from Brazil so far.…”
Section: Discussionmentioning
confidence: 92%